1987
DOI: 10.1210/endo-121-2-520
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism and Abnormalities in the Kinetics of Thyroid Hormone Metabolism in Rats Treated Chronically with Polychlorinated Biphenyl and Polybrominated Biphenyl*

Abstract: Studies were directed at the question of whether polychlorinated biphenyl (PCB; Aroclor 1254) and polybrominated biphenyl (PBB; Fire Master BP-6), when administered in the diets of female Sprague-Dawley rats over long periods of time (5-7 months) and at low dosages (0, 1, 5, 10, and 50 ppm), would depress the thyroid. By examining serum T3 and T4, kinetics of T4 metabolism, and in vivo thyroid response to exogenous TSH injections, an estimate of the degree of hypothyroidism was made, and abnormalities in T4 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(67 citation statements)
references
References 24 publications
4
61
1
1
Order By: Relevance
“…(2) PCBs may directly inhibit the thyroid gland. It has been shown in rats that the thyroidal response to exogenous TSH was reduced in response to PCBs (Byrne et al, 1987). This suggests that PCBs may inhibit the thyroid gland directly rather than inhibiting function of the HPT axis.…”
Section: Chapter 5: Discussionmentioning
confidence: 99%
“…(2) PCBs may directly inhibit the thyroid gland. It has been shown in rats that the thyroidal response to exogenous TSH was reduced in response to PCBs (Byrne et al, 1987). This suggests that PCBs may inhibit the thyroid gland directly rather than inhibiting function of the HPT axis.…”
Section: Chapter 5: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that these environmental contaminants can alter various aspects of thyroid function in several vertebrate species (e.g., Brouwer et al 1989;Byrne et al 1987;Chiba et al 2001;Collins et al 1977;Collins and Capen 1980a, 1980b, 1980cDesaulniers et al 1999;Langer et al 1998;Schumacher et al 1993;Sepkovic and Byme 1984;Tryponas et al 1984). The cellular mechanisms involved in thyroid pathology are poorly known.…”
Section: Discussionmentioning
confidence: 99%
“…Among the primary effects of PCBs on thyroid hormone metabolism demonstrated so far are the displacement of thyroid hormones from plasma protein binding, an increase in their conjugation in the liver and interference with their intracellular metabolism (4,5,7,8,11). …”
Section: European Journal Of Endocrinology (1998) 139mentioning
confidence: 99%
“…Since these were distinct from those observed after short-and long-term thyroid-stimulating hormone (TSH) stimulation, they were considered to result from direct damage to the thyroid (6). Direct effects of PCBs on the thyroid are supported by the decreased effect of TSH on T 4 and triiodothyronine (T 3 ) release from the thyroid in rats pretreated with PCBs when compared with controls (7).…”
Section: Introductionmentioning
confidence: 99%